Free Radical Cyclization of N-Arylacrylamides: Mild and Facile Synthesis of 3-Thiocyanato Oxindoles - Karmaker, Pran Gopal; Qiu, Jiashen; Wu, Di; Yin, Hongquan; Chen, Fu-Xue (Synlett, 2018)
A novel and convenient oxidative radical cyclization of N-substituted N-arylacrylamides for the synthesis of 3-thiocyanated oxindoles has been developed by using AgSCN and K2S2O8 as the radical source. This process allows a consistent and convenient access to SCN-containing heterocycles bearing a broad range of functional groups in good to excellent yields (up to 91%). Moreover, the use of inexpensive and readily available starting materials, operational simplicity, and excellent functional group tolerance makes this protocol practically attractive.
Keywords: alkenes; oxindole; radical cyclization; silver; tandem reaction; thiocyanation